A Qualitative Inquiry into the Socio-Economic Determinants of English Learning Motivation among University Students - Wijaya, Ahmad Krisnawan; Feri Ferdiyanto; Zainuddin, Zainuddin (Journey: Journal of English Language and Pedagogy, 2026)
The present research seeks to explore how certain social and economic factors affect the motivational process of learning English among university students at Islamic Zainul Hasan Genggong University. A qualitative case study was chosen as the research methodology, and data were collected through written interviews with 10 students from the Department of English Education across various semesters. Thematic analysis was used to analyze the data. From the results, it can be noted that students’ motivation is shaped by interactions among factors such as family influence, peer environment, exposure to technology, and economic conditions. Family expectations and cultural norms contribute to instilling a sense of responsibility and commitment to studies in students. Peer involvement and digital communication provide further avenues for exposure to the target language. Financial pressures, on the one hand, make learning difficult owing to the lack of necessary study materials and increased stress, while on the other hand, they motivate the students to learn English so as to secure better job opportunities in the future.